Laparoscopic pyelolithotomy/ureterolithotomy combined with flexible ureterorenoscopy for upper urinary tract stones especially in anomalous kidneys - Olcucuoglu, Erkan; Taha Olcucu, Mahmut; Tonyali, Senol; Olcucuoglu, Esin; Odabas, Oner (Annals of Medical Research, 2021)
Aim: To determine the feasibility and efficacy of combining laparoscopy with flexible ureteroscopy to achieve stone free status especially in patients having large pelvic renal stones in their anomalous urinary tract.Material and Methods: We retrospectively reviewed the medical records of all patients who underwent laparoscopic pyelo/uretero- lithotomy in our clinic between March 2013 and December 2017.Results: A total of 24 patients were included the study. The mean age of the patients was 49.7 years ranging from 20 to 75 years. Pyelolithotomy was performed in 17 cases and ureterolithotomy was performed in 7 cases. The mean size of the main upper urinary tract stones (pelvis and upper ureter) was 40 mm and the mean size of the concomitant stones (renal pelvis and calices) was 8.5 mm. Of the pyelolithotomy patients, six had ureteropelvic junction (UPJ) obstruction, seven had a horseshoe kidney and one had a pelvic kidney abnormality. Pyeloplasty was performed concomitant with stone surgery in patients with UPJ obstruction. The mean operative time was 122 min. Estimated blood loss was 55 ml. Stone - free status was 91.6%. There was no intraoperative complication. The mean hospital stay of the patients was 4 days.Conclusion: Laparoscopic pyelolithotomy/ureterolithotomy combined with flexible endoscopy (cystoscope) for renal pelvis and caliceal stones is a safe and effective procedure to achieve stone free status especially in patients having congenital anomalous kidneys.